(untitled) (Journal of the Sociology and Theory of Religion, 2025)
During the second half of the 20th century, a popular theological and doctrinal movement emerged in the Catholic Church, especially in Ibero-America (liberation theology), whose main aim was to establish a Marxist messianism. Two political and economic models will be examined by the Faith. We will analyse this theological and economic debate, and whether this dilemma has been reopened in the Catholic world today. What is the Catholic moral foundation of private property? Does market freedom deserve the intervention of the public authorities in order to objectify the divine mandate that exalts the underdog and humiliates the powerful? Who lives: The God of freedom or the God of liberation?